Методологічні підходи до формування виробничої стратегії підприємства - Васильченко, Олена Олегівна; Васильченко, Елена Олеговна; Vasylchenko, Olena; Попова, Тетяна Вікторівна; Попова, Татьяна Викторовна; Popova, Tetiana (My University, 2017)
UK: У сучасному конкурентному середовищі при визначенні товарного асортименту ключовим є аналіз поведінки споживача. При дослідженні специфіки споживання круп враховано дві основні ознаки: вік та рівень доходів. У результаті проведення експертного аналізу було визначено, що основними клієнтами є достатньо забезпечені споживачі середнього та зрілого віку. Проведене дослідження показало, що підприємствам, які займаються виробництвом круп у даному споживчому сегменті, рекомендується враховувати переваги споживачів кожної вікової групи. EN: The analysis of consumer behavior is a key in determining product lines in today's competitive environment. It was revealed that consumers choose cereals using their criteria such as the nutritional property and the chemical composition; the manufacturing technology; the shape, the size and the color; the flavoring properties; the assortment; the expiration date. During the study of the specific consumption of cereals two main characteristics of consumers such as age and income were taken into consideration. The results of expert analysis determined that the main customers are wealthy ones at the age from 26 to 45 and from 46 to 60. The level of income was taken as a basis of segmentation. It was found that low-income consumers with an average income and nutrition representatives focus on the price of cereals. For groups with high incomes the most important factors are cereals tastes, their exteriors and manufacturing technology. Stores focus on the factors related to the sales. It was determined that cereal TM "Hutorok" was the most popular product with consumers at the age from 18 to 30 years and retired customers. Other people didn’t pay attention to the brand of cereals, because they believed in equally beneficial consumption. The research showed that buckwheat and peas were the most popular products with consumers at the age from 18 to 30 years. Consumers at the age from 31 to 40 years and from 41 to 60 years preferred buckwheat. The oldest group of surveyed respondents didn’t take into consideration the brand of the product. Thus, the formation of the enterprise production structure is carried out in several stages. They are an identification of the main product criteria for consumption; consumer demands of the major segments of customers by gender and frequency of cereals using, which allow you to determine the level of product demand and the consumer sex dependence; popularity of cereals brands with various age groups; the demand for certain type of products within product lines. The study justified recommendations for the companies engaged in the cereal production. It is highly recommended for companies to take into consideration consumer preferences of various age groups.
Methodological approach to the formation of the enterprises strategy production
Keywords: споживчий вибір; критеріїв споживання круп; потреби; сегментування ринку; сегментування ринку; товарний асортимент; виробнича стратегія; consumer choice; criteria of cereals consumption; needs; segmentation of the market; consumer demand; range of products; production strategy